Impact of Culture on Management of Foreign SMEs in China - Pauluzzo, Rubens (International Series in Advanced Management Studies,, 2018)
This book describes how a deeper knowledge and understanding of cultural differences represents a meaningful and useful tool for management of companies, and in particular SMEs, in the People's Republic of China. After introductory chapters on the internationalization of SMEs and the role played by management in this process, the authors explore the implications of academic discourses on culture and its dimensions for company management. The influence of Chinese cultural roots and the country's current cultural environment on management is then examined, with provision of guidance on response to the identified challenges. A key feature of the book is the presentation of important recent fieldwork in the main economic regions of China. This research further clarifies how business culture and cultural differences impact on company activities in China and casts light on various aspects of the adaptive capability of SMEs within the country, highlighting the value of cultural awareness and intelligence. The book will be of interest to academics and practitioners alike.